STRATEGI PENINGKATAN GREEN CUSTOMER LOYALTY UNTUK PRODUK AIR MINERAL KEMASAN RAMAH LINGKUNGAN DI PULAU JAWA - Khilyatin Ikhsani; Miswan Gumanti; Fauzi (JMBI (Journal of Marketing and Business Intelligence), 2025)
This study aims to bridge the practical gap in enhancing green customer loyalty for environmentally friendly products by identifying the key influencing factors. The research adopts a descriptive quantitative approach involving 400 respondents selected using non-probability sampling, specifically purposive sampling. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.2.6 software. The findings reveal that green product quality and green branding have a direct and significant effect on green customer satisfaction. Furthermore, green customer satisfaction is proven to mediate the relationship between green product quality and green branding on green customer loyalty. These results highlight the critical role of environmentally friendly product quality and green branding strategies in fostering customer satisfaction and loyalty. The theoretical contribution of this study lies in proposing a novel conceptual model within the context of eco-friendly bottled drinking water products, thereby enriching the marketing management literature, particularly in sustainable consumer behavior. Practically, the findings provide strategic implications for companies in designing sustainability-oriented marketing policies to enhance customer loyalty toward green products.